Magnetic macro drivers of trade openness: a study of BRICS economies - Suleman, Shahida; Mohd Thas Thaker, Hassanudin; Cheong, Calvin Wing Hoh (Sage Journals, 2024)
The major goal of this study endeavour is to thoroughly evaluate the impact of macro factors on trade openness (TOP). The study was conducted through the examination of numerous trade conceptions, with a specifically emphasis on examining these patterns within the economies of the BRICS nations (Russia, India, China and South Africa) from 1995 to 2020. Stepwise regression for selecting models, Pedroni, Johnson, Granger causality and advance panel regression are some of the techniques used including FMOLS, Panel OLS and FEM. The study’s outcomes reveal the presence of both long-term and short-term associations between TOP and (a) total investment, (b) human capital, (c) trade reserves, (d) trade balance and (e) exchange rate. The study authors found both one-way and two-way causal association between TOP and these five factors. Additionally, trade balance emerges as the most significant factor impacting TOP. Notably, the exchange rate does not exhibit significant economic importance.